Effects of alkali and transition metal-doped TiO2 hole blocking layers on the perovskite solar cells obtained by a two-step sequential deposition method in air and under vacuum - Nwankwo, U.; Ngqoloda, Siphelo; Nkele, Agnes C.; Arendse, Christopher J.; Ozoemena, Kenneth I.; Ekwealor, A. B. C.; Rajan, Jose; Maaza, Malik; Ezema, Fabian I. (Royal Society of Chemistry, 2020)
Planar perovskite solar cells (PPSCs) have received great attention in recent years due to their intriguing properties, which make them a good choice for photovoltaic applications. In this work, the effect of alkali and transition metal-doped TiO2 (cesium-doped TiO2 (Cs-TiO2) and yttrium-doped TiO2 (Y-TiO2)) compact layers on the optical, structural and the photovoltaic performance of the PPSCs have been investigated. The perovskite layer syntheses were carried out by depositing a lead iodide (PbI2) layer via spin-coating; converting PbI2 into methyl ammonium iodide (CH3NH3PbI3) by chemical vapor deposition (CVD) and spin-coating at 60 min and 60 s conversion times respectively. The as-deposited PPSCs were studied layer-by-layer using an X-ray diffractometer, scanning electron microscope, and UV-vis diffuse reflectance, transmittance and absorbance. The power conversion efficiency for stable processed perovskite solar cells were 3.61% and 12.89% for air and vacuum processed, respectively.